PENINGKATAN KOMPETENSI ISLAMI BERWAWASAN LINGKUNGAN MAHASISWI UNIVERSITAS MUHAMMADIYAH PALANGKARAYA MELALUI KULIAH KERJA NYATA - Ady Ferdian Noor; Bulkani Bulkani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
Student competency is a skill that must be developed through the Community Service Program (KKN). KKN Muhammadiyah University of Palangkaraya carried out according to the Master Plan Development of PkM and modified with the Motto of Muhammadiyah University of Palangkaraya: "The Green Islamic Campus" Islamic Campus with the Environment and with focus on PKM activities conducted by Student. Competence is important to keep in mind. McAnhan (1981) argues that competence is a knowledge, skill, and capability possessed by someone who has become a part of himself to color his cognitive, affective, and psychomotor behavior (Sanjaya, 2008). PKM this time at the Community Service Program in the business charity Muhammadiyah University of Palangkaraya led to the fact that women can carry out the work normally done by men. The activities include physical activity helping to create a yard with paving, cementing, sifting sand, planting trees, cleaning sewers and trash, sweeping; non-physical activities teaching or dancing or giving lectures on the ideal family. Women are the very active role and really take advantage of all the knowledge and energy in improving competence while maintaining the limit etiquette. The objective of KKN is to create students who have the competence to be able to work in terms of supporting the greening movement and keep dressing and behaving in an Islamic way.